Epigenetic Priming Confers Direct Cell Trans‐Differentiation From Adipocyte to Osteoblast in a Transgene‐Free State. Issue 7 (17th December 2015) - Cho, Young‐Dan; Bae, Han‐Sol; Lee, Dong‐Seol; Yoon, Won‐Joon; Woo, Kyung‐Mi; Baek, Jeong‐Hwa; Lee, Gene; Park, Joo‐Cheol; Ku, Young; Ryoo, Hyun‐Mo
Abstract : The bone marrow of healthy individuals is primarily composed of osteoblasts and hematopoietic cells, while that of osteoporosis patients has a larger portion of adipocytes. There is evidence that the epigenetic landscape can strongly influence cell differentiation. We have shown that it is possible to direct the trans‐differentiation of adipocytes to osteoblasts by modifying the epigenetic landscape with a DNA methyltransferase inhibitor (DNMTi), 5′‐aza‐dC, followed by Wnt3a treatment to signal osteogenesis. Treating 3T3‐L1 adipocytes with 5′‐aza‐dC induced demethylation in the hypermethylated CpG regions of bone marker genes; subsequent Wnt3a treatment drove the cells to osteogenic differentiation. When old mice with predominantly adipose marrow were treated with both 5′‐aza‐dC and Wnt3a, decreased fatty tissue and increased bone volume were observed. Together, our results indicate that epigenetic modification permits direct programming of adipocytes into osteoblasts in a mouse model of osteoporosis, suggesting that this approach could be useful in bone tissue‐engineering applications. J. Cell. Physiol. 231: 1484–1494, 2016. © 2015 Wiley Periodicals, Inc.